Miniaturization of UWB Antennas on Organic Material - Symeon Nikolaou; Muhammad Ali Babar Abbasi (International Journal of Antennas and Propagation)
Three planar, CPW-fed, UWB antennas with increasingly reduced size are presented and the miniaturization method is discussed. The first antenna is a CPW-fed elliptical slot with an uneven U-shaped tuning stub, the second antenna is a cactus shaped monopole, and the third one is a miniaturized version of the cactus shaped monopole antenna. All presented antennas have a simulated and measured return loss below −10 dB over the 3.1 to 10.6 GHz UWB frequency range and mostly omnidirectional radiation patterns. The proposed antennas are fabricated on liquid crystal polymer (LCP). The CPW-fed slot antenna requires an overall board dimension of 38 mm × 40 mm, and the evolved cactus monopole is confined in a 28 mm × 32 mm board, while the final miniaturized cactus monopole is printed on 28 mm × 20 mm board, resulting in a 41% and 63% size reduction, respectively. Using both simulations and measurements, the paper analyzes the response of all three antennas and discusses and demonstrates the effectiveness of the implemented miniaturization method.